Retromastoid osteoma—a rare case report. Issue 1 (13th January 2020) - Tan, Edmund Wooi Keat; Barco, Jason Bae; Rehman, Mutee Ur; Tan, Choon Chieh
Abstract: Osteomas are slow growing bone tumours and are often asymptomatic. Rarely, they can be present in the temporal bone—only few cases had been reported, with an incidence of 0.1–1%. We describe a case of an osteoma of the temporal bone (retromastoid) found in a 40 year old female, who presented with a slow growing swelling behind the right ear for 9 years. Diagnosis was made on non-contrast computed topography (CT) of the skull. Treatment is indicated in symptomatic cases or cosmetic reasons. Screening colonoscopy and genetic testing for familial adenomatous polyposis (FAP) and Gardner's syndrome are advised.